A Systematic Literature Review and Integrative Meta-Analytic Synthesis on Virtual Reality for Pencak Silat Education (2015–2025) - Didik Cahyono; Johnlenon N. Aliser; Sri Sumartiningsih; Hadi Hadi (Journal of Innovative and Creativity, 2025)
The rapid advancement of digital technology has created new opportunities for innovation in education, particularly through virtual reality (VR), which serves as an immersive learning medium. While numerous studies have explored the pedagogical potential of VR in science and health education, its application in traditional martial arts such as Pencak Silat remains under-researched. This study systematically reviews and synthesizes global evidence on the effectiveness of VR-based learning within physical education contexts using the PRISMA 2020 framework. Literature searches were conducted across Scopus and ScienceDirect databases for publications from 2015 to 2025. Ten eligible studies were identified, including six meta-analyses and four systematic thematic reviews. Quantitative findings revealed that VR produced small to moderate improvements in knowledge (SMD = 0.28–0.97) and practical skills (SMD = 0.15–0.23), with significant effects on complex cognitive domains (SMD = 1.12) and learning satisfaction (SMD = 1.14). Thematic analyses highlighted consistent enhancements in learner motivation, engagement, and self-efficacy, though methodological heterogeneity and limited experimental validation in martial arts education persist. Specifically, research on Pencak Silat remains at a developmental stage, with an emphasis on media design rather than empirical evaluation. The synthesis concludes that VR offers strong pedagogical potential to enhance physical education’s cognitive, psychomotor, and affective learning outcomes. Nevertheless, future research should implement robust experimental designs and objective motion-based assessments to evaluate skill transfer and preserve cultural values in Pencak Silat learning within junior high schools.